Suicídio: Justificabilidade moral a partir do pensamento de David Hume - Pereira, Jane Santana (My University, 2020)
In this thesis, the main objective is to reflect about the moral justificability of suicide starting from David Hume’s theory. Suicide represents a disturbing phenomenon that is inserted in the historical-philosophical context and emphasizes the importance of research, discussions and reflections in contemporary society. The justification of this work is the need to conceive a causal relationship for suicide, that is, a prediction of cause and effect for the fact. With this, intervene in the breaking of taboos, prevention and awareness of society on the subject. The philosophical question is whether suicide is a morally justifiable act from the thought of David Hume. For this, we intend to analyze the theoretical foundation of morality and the possibility of exposing its empirical method and its understanding in the philosophical context. In this sense, the present dissertation intends to analyze a truly serious philosophical problem: Suicide and moral justification. In addition, specific objectives were defined to describe suicide from the perspectives of health, sociology, philosophy, and to understand David Hume's experimental method of reasoning for moral issues, analyzing empiricism, morality, causality, and unique experiences for social, political and personal criterion of suicide. To better understand, theoretical support was sought in the author's main work, The Treatise of Human Nature and Essays, Morals, Politicians and Literary where the related texts “Of Suicide” are found. As a research methodology, we used the theoretical support of the authors who talk about the problem of suicide as a human conduct. In the first moment, a historical-philosophical approach about suicide, its incidence and considerations is presented. Next, there is a contextualization from the viewpoint of health, sociology and philosophy. In the second moment, we present the Humean philosophy and the construction of morality: the empirical method. In the third and last moment, we highlight David Hume's ideas applied to the moral justification of suicide, as well as the use of reason and sensitivity to prove its truth.
O objetivo principal desta dissertação é refletir acerca da justificabilidade moral do suicídio a partir da teoria de David Hume. O suicídio representa um fenômeno perturbador encontra-se inserido no contexto histórico-filosófico e ressalta a importância das pesquisas, discussões e reflexões na sociedade contemporânea. A questão filosófica é: o suicídio é um ato moralmente justificável a partir do pensamento de David Hume? Para isso, pretende-se analisar a fundamentação teórica da moral e a possibilidade de expor o seu método empírico e a sua compreensão no contexto filosófico. Nesse sentido, a presente dissertação tem a pretensão de analisar um problema filosófico verdadeiramente sério: O suicídio e a justificabilidade moral. Para melhor compreender buscou-se apoio teórico na principal obra de Hume, O Tratado da natureza humana e Ensaios, Morais, Políticos e Literários. Como metodologia de pesquisa, utilizou-se um apoio teórico dos autores que dissertam sobre a problemática do suicídio como conduta humana. No primeiro momento, apresenta-se uma abordagem histórica-filosófica acerca do suicídio, sua incidência e considerações. Na sequência, consta uma contextualização sob a visão da área da saúde, da sociologia e da filosofia. No segundo momento, apresenta-se a filosofia Humeana e a construção da moralidade: o método empírico. No terceiro e último momento, destacam-se as ideias de David Hume aplicadas à justificabilidade moral do suicídio, bem como o uso da razão e a sensibilidade, para comprovar a sua verdade.
Keywords: Hume, David, 1711-1776; Suicídio; Filosofia; Ética; Suicide; Philosophy; Ethics